2014
DOI: 10.1111/rda.12255
|View full text |Cite
|
Sign up to set email alerts
|

Antral Follicle Populations and Embryo Production – In Vitro and In Vivo – of Bos indicus–taurus Donors from Weaning to Yearling Ages

Abstract: Interest in indicus-taurus cattle has been increasing, as these animals are likely to present the best characteristics of Zebu and European bovine breeds. The aim of this study was to compare the embryo production of indicus-taurus donors with high vs low antral follicle counts obtained by ovum pickup/in vitro production (OPU/IVP) and superovulation (SOV)/embryo collection. Braford females at weaning age (3/8 Nelore × 5/8 Hereford, n = 137, 9 ± 1 month old) were subjected to six serial ovarian ultrasonographs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 22 publications
6
44
1
4
Order By: Relevance
“…The number of recruited follicles in each follicular wave is highly variable between individuals; however, a high level of individual repeatability is observed (Evans et al, 2010;Oliveira Junior et al, 2015;Batista et al, 2014;Gobikrushanth et al, 2017). High correlation of AFP with in vivo and in vitro embryo production may be used as an auxiliary tool to select donor cows for embryos and oocytes (Silva-Santos et al, 2014a;Baruselli et al, 2015;Ghanem et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The number of recruited follicles in each follicular wave is highly variable between individuals; however, a high level of individual repeatability is observed (Evans et al, 2010;Oliveira Junior et al, 2015;Batista et al, 2014;Gobikrushanth et al, 2017). High correlation of AFP with in vivo and in vitro embryo production may be used as an auxiliary tool to select donor cows for embryos and oocytes (Silva-Santos et al, 2014a;Baruselli et al, 2015;Ghanem et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent counts were performed twice at 35-day intervals without synchronization and in accordance with other studies (CUSHMAN et al, 2009;SILVA-SANTOS et al, 2014a), no influence of stage of estrous cycle on OAFPs was observed. However, based on consideration of ovary characteristics as well as the historical age at puberty for Girolando and Nelore breeds in the study region, heifers were considered to be prepubertal at the time of the study and were therefore not subjected to the estrus synchronization treatment administered to cows.…”
Section: Discussionmentioning
confidence: 81%
“…For cattle, improved success of in vitro embryo production has been associated with high numbers of recovered cumulus oophorus complexes (COCs) from bovine females (PONTES et al, 2011;SILVA-SANTOS et al, 2014a, 2014b. However, high individual and between-breed variations in oocyte production have been observed and researchers seek to identify mechanisms underlying such variability.…”
Section: Discussionmentioning
confidence: 99%
“…Estes resultados foram suportados por diversos pesquisadores, que também verificaram inter-relação entre estes parâmetros (CUSHMAN et al, 2009;IRELAND et al, 2008;MOSSA et al, 2012). A literatura demonstrou ainda que fêmeas apresentando um maior DOV tiveram maior número de folículos e oócitos saudáveis (IRELAND et al, 2008;SILVA-SANTOS et al, 2014).…”
Section: Resultsunclassified
“…Contagem de folículos antrais (CFA) (Média±EP) P-valor (IRELAND et al, 2007(IRELAND et al, , 2008JIMENEZ-KRASSEL et al, 2009;SILVA-SANTOS et al, 2014). Acreditava-se que os resultados desta pesquisa iriam confirmar estas evidências fisiológicas, porém, neste estudo, o efeito da CFA sobre a fertilidade não foi observado.…”
Section: Número De Animaisunclassified